2021
DOI: 10.1038/s41370-021-00369-7
|View full text |Cite
|
Sign up to set email alerts
|

Proximity to coal-fired power plants and neurobehavioral symptoms in children

Abstract: Background Coal-fired power plants are a major source of air pollution that can impact children’s health. Limited research has explored if proximity to coal-fired power plants contributes to children’s neurobehavioral disorders. Objective This community-based study collected primary data to investigate the relationships of residential proximity to power plants and neurobehavioral problems in children. Methods 235 participants aged 6–14 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Unexpectedly, Cox regression showed that the association between coal use and the risk of childhood stunting was not significant during follow-up, although several studies have confirmed the effect of coal on the health status of children ( 43 45 ). We thought that it might be related to a much lower use of coal than biofuels in this study, and the inadequate sample size of coal use.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, Cox regression showed that the association between coal use and the risk of childhood stunting was not significant during follow-up, although several studies have confirmed the effect of coal on the health status of children ( 43 45 ). We thought that it might be related to a much lower use of coal than biofuels in this study, and the inadequate sample size of coal use.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to air, fugitive emissions can contaminate the soil in the area immediately surrounding the power plant, , as well as areas as far away as 30 km . CCR air pollution is a known inhalation health hazard due to small airborne particulates (<0.25 μm diameter) and has been associated with higher morbidity and respiratory and cardiovascular disease. A growing body of survey-based studies has shown that children living near power plants may experience increased respiratory problems and neurobehavioral disorders. One recent study using direct measurements found an association between residence proximity to CCR disposal sites and the concentrations of Fe, Al, and silicon (Si) in children’s nails. The concentration of Cr, Mn, and zinc (Zn) in the children’s nails were also higher than literature-reported values for non-CCR exposed children …”
Section: Future Perspectivesmentioning
confidence: 99%
“…The coal power plants’ associated health issues have been widely discussed. Zhang et al, ( 2022 ) described there has been a significant relationship between the proximity to the coal power plant and neurobehavioral problems (e.g., social problems, affective problems, and anxiety problems) among kids through a study of two coal power plants (Cane Run and Milk Creek power plants) in Kentucky, USA.…”
Section: Socio-environmental Vulnerability To Environmental Pollution...mentioning
confidence: 99%